Research progress of zebrafish heart regeneration models - ZHANG Weijia; LIANG Jinxiu; HAN Peidong (浙江大学学报. 农业与生命科学版)
Heart disease is a major threat to human health due to the high morbidity and mortality rates. As a result, the discovery of adult zebrafish heart regeneration provides a new perspective for the study and treatment of human heart diseases. This study reviewed the zebrafish heart injury models for heart regeneration, such as apex amputation, cryoinjury, genetic ablation of cardiomyocyte models and so on. In addition, we also explored the essential mechanisms underlying heart regeneration, including the spatiotemporal activation of multiple signaling pathways in different cell types, epigenetic reprogramming, coronary revascularization, activation of key development-related transcription factors, and the disassembly and reassembly of cardiomyocyte sarcomeric structure. Analysis of the mechanism of heart regeneration provides more references basis for therapeutic strategies to overcome heart disease in the future.